Projecting order in the pericolonial Philippines: An anthropology of Catholicism beyond Catholics - Paredes, Oona (The Australian journal of anthropology, 2017)
In a majority Catholic country like the Philippines, it can be difficult to appreciate the true impact of Catholicism, beyond the obvious presence of Catholics. For the ‘unchristianised’ indigenous minorities in its peripheral upland regions, the role of the Catholic thought-world in shaping who they are today is masked substantially by their cultural distinctiveness. Missionary-dominated narratives in colonial historiography configure our understanding of the present, structuring our approach to anthropology in these peripheral spaces. This article argues that the diachronic component is necessary to make sense of how Catholicism has not only shaped the diversity of modern Philippine cultures, but also how it has configured cultural and political spaces so completely that, as anthropologists, we at times reproduce this thought-world uncritically through our own ethnographies. A focus on the so-called unchristianised Lumad ethnic minorities of Mindanao argues that it is essential to look beyond Catholics as obvious subjects when undertaking an anthropology of Catholicism.